Influence of massage, active and passive recovery on swimming performance and blood lactate - Ali Rasooli, S.; Koushkie Jahromi, M.; Asadmanesh, A.; Salesi, M. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM: Recovery is an important part of athletic training. The aim of this study was to evaluate influences of three methods of recovery including massage, active and passive recovery on blood lactate concentration and subsequent swimming performance of elite swimmers. METHODS: Seventeen professional male swimmers (age:21± 2.4 years, height: 175.35±9.1 cm, weight: 67.66± 11.88 kg) voluntarily participated in this study. Two Swimming trials performed in every session which involved 200 m of front crawl swimming with maximal effort separated by ten minutes interval (recovery) period. Statistical method of repeated measures was used for analysis of data. RESULTS: There was significant difference in blood lactate after three types of recovery. CONCLUSION: the results indicated that active recovery was more effective than massage and massage was more effective compared to passive recovery in removing blood lactate. Active and massage recovery were more effective in improving swimming performance than passive recovery.